In vivo RNAi in the drosophila follicular epithelium: analysis of stem cell maintenance, proliferation, and differentiation - Riechmann, Veit (RNAi and Small Regulatory RNAs in Stem Cells, 2017)
In vivo RNAi in Drosophila facilitates simple and rapid analysis of gene functions in a cell- or tissue-specific manner. The versatility of the UAS-GAL4 system allows to control exactly where and when during development the function of a gene is depleted. The epithelium of the ovary is a particularly good model to study in a living animal how stem cells are maintained and how their descendants proliferate and differentiate. Here I provide basic information about the publicly available reagents for in vivo RNAi, and I describe how the oogenesis system can be applied to analyze stem cells and epithelial development at a histological level. Moreover, I give helpful hints to optimize the use of the UAS-GAL4 system for RNAi induction in the follicular epithelium. Finally, I provide detailed step-by-step protocols for ovary dissection, antibody stainings, and ovary mounting for microscopic analysis.